Three new vanadyl(IV) complexes with non-steroidal anti-inflammatory drugs (Ibuprofen, Naproxen and Tolmetin) - Etcheverry, Susana B. (2002)
The synthesis and spectral and magnetic characterization of VO(2+) complexes with Ibuprofen (2-(4-isobutylphenyl)propionic acid), Naproxen (6-methoxy-alpha-methyl-2-naphthalene acetic acid) and Tolmetin (1-methyl-5-(4-methylbenzoyl)-1H-pyrrole-2-acetic acid) were studied. The complexes [VO(Ibu)(2)] x 5CH(3)OH, [VO(Nap)(2)] x 5CH(3)OH and [VO(Tol)(2)] were obtained from methanolic solutions under nitrogen atmosphere. The biological activities of these complexes on the proliferation of two osteoblast-like cells in culture (MC3T3E1 and UMR106) were compared with that of the vanadyl(IV) cation. The complexes exhibited different effects depending on the concentration and the cellular type, while no effect was observed for their parent drugs.